2007
DOI: 10.1167/7.2.18
|View full text |Cite
|
Sign up to set email alerts
|

How odgcrnwi becomes crowding: Stimulus-specific learning reduces crowding

Abstract: Processes underlying crowding in visual letter recognition were examined by investigating effects of training. Experiment 1 revealed that training reduces crowding mainly for trained strings. This was corroborated in Experiment 2, where no training effects were obvious after 3 days of training when strings changed from trial to trial. Experiment 3 specified that after a short amount of training, learning effects remained specific to trained strings and also to the trained retinal eccentricity and the interlett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 30 publications
5
34
0
1
Order By: Relevance
“…Research on crowding should therefore consider the differential effects that it may have on action. Do the training effects found in perceptual crowding translate to better visuomotor resolution as well (Green and Bavelier, 2003, 2007; Chung, 2007; Huckauf and Nazir, 2007)? If so, perceptual training within cluttered scenes may improve visuomotor performance in individuals with central field visual loss (e.g., Timberlake et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Research on crowding should therefore consider the differential effects that it may have on action. Do the training effects found in perceptual crowding translate to better visuomotor resolution as well (Green and Bavelier, 2003, 2007; Chung, 2007; Huckauf and Nazir, 2007)? If so, perceptual training within cluttered scenes may improve visuomotor performance in individuals with central field visual loss (e.g., Timberlake et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Following brain lesions, such encoding may be lost, resulting in "note-by-note" reading (Stanzione et al, 1990). Expertise in word reading involves analogous perceptual tuning, namely reading-selective reduction of crowding (Huckauf and Nazir, 2007; M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT Pelli and Tillman, 2008), and synthetic perception of complex objects such as frequent groups of letters (Vinckier et al, 2007;Grainger and Ziegler, 2011).…”
Section: Correlates Of Musical Expertisementioning
confidence: 99%
“…Support for such a notion can be found in the results of several studies in which a reduction in crowding was obtained through training (Chung, 2007;He, Legge, & Yu, 2013;Huckauf & Nazir, 2007;Hussain, Webb, Astle, & McGraw, 2012;Sun, Chung, & Tjan, 2010). In the two studies where a lower level of crowding for letters was found (Chanceaux & Grainger, 2012;Grainger et al, 2010), the stimuli were presented in the part of the visual field where reading normally takes place (the horizontal meridian in the parafovea) and in the standard text format (horizontal strings).…”
Section: Introductionmentioning
confidence: 99%